2015
DOI: 10.1039/c4cs00487f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle colloidal stability in cell culture media and impact on cellular interactions

Abstract: Nanomaterials are finding increasing use for biomedical applications such as imaging, diagnostics, and drug delivery. While it is well understood that nanoparticle (NP) physico-chemical properties can dictate biological responses and interactions, it has been difficult to outline a unifying framework to directly link NP properties to expected in vitro and in vivo outcomes. When introduced to complex biological media containing electrolytes, proteins, lipids, etc., nanoparticles (NPs) are subjected to a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
743
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 854 publications
(767 citation statements)
references
References 190 publications
20
743
1
3
Order By: Relevance
“…In this study, aggregation of Fe 3 O 4 NPs was observed in culture media, and induced ROS production in a dose-dependent manner. Thus, this is an interesting, leading that complex of MNPs, a chemotherapeutic agent and FBS may effect on interactions such as cellular uptake via alternative endocytosis pathways [26]. However, there remains a problem to be solved by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, aggregation of Fe 3 O 4 NPs was observed in culture media, and induced ROS production in a dose-dependent manner. Thus, this is an interesting, leading that complex of MNPs, a chemotherapeutic agent and FBS may effect on interactions such as cellular uptake via alternative endocytosis pathways [26]. However, there remains a problem to be solved by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we have presented different methods that are nowadays used for the detection and quantification of plasmonic NPs in physiological fluids. In order to understand NP behavior in physiological environments, it is not enough to only supply robust and universal characterization methods but also to be aware of their limitations, and apply, whenever possible, more than one technique [41].…”
Section: Discussionmentioning
confidence: 99%
“…This additionally highlights the necessity of taking into account sedimentation and diffusion, which can vary wildly for aggregates. In a recent review, we have described the current state-of-the art, the theory behind it, current bottlenecks in this field [41].…”
Section: Cell Culture Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, several analytical methods such as dynamic light scattering (DLS), NP tracking analysis (NTA), UV-Vis spectroscopy, field-flow fractionation, analytical ultracentrifugation, and transmission electron microscopy (TEM) have been utilized to characterize NP sizes and size distributions [4][5][6][7][8]. Each method has its advantages and disadvantages, and a combination of techniques is typically recommended to adequately characterize NPs [4]. For example, TEM provides information about NP core sizes, but cannot evaluate NP hydrodynamic diameters.…”
Section: Introductionmentioning
confidence: 99%